Dynamics of the phospholipid shell of microbubbles: a fluorescence photoselection and spectral phasor approach. Issue 38 (26th April 2018) - Slenders, Eli; Seneca, Senne; Pramanik, Sumit Kumar; Smisdom, Nick; Adriaensens, Peter; vandeVen, Martin; Ethirajan, Anitha; Ameloot, Marcel
Abstract : The lipid organization of microbubbles is important in many applications. Abstract : The lipid organization of microbubbles is important in many applications. By monitoring the photoselection and emission spectrum of the fluorescent probe Laurdan in perfluorobutane gas-filled DPPC microbubbles with a two-photon laser scanning microscope, we observed a transition to a more rigid lipid organization in 30 minutes to several hours.